Chaetomitrium Laevisetum - Monica Suleiman; Hiroyuki Akiyama (2014)
This species is identical to C. roemeri M.Fleisch. except for its shorter branch leaf acumen and the longer seta. The seta of the holotype of C. roemeri is only 10 mm, while those of C. laevisetum are reaching 25 mm in length. This species might be just a variant of C. roemeri. We temporarily treat it as a separate species here.